Blocking footwork techniques used by male and female volleyball players are different - Lobietti, R.; Merni, F. (Journal of Human Movement Studies, 2006)
The purpose of this study was to determine tendencies in lateral footwork techniques used by Volleyball players when blocking. Videos of 16 female and 15 male matches from the 2004-2005 season of the Italian Professional Leagues were analysed and the blockers' movements were classified. The seven techniques identified (slide Step, cross-over, vertical jump, repeated slides, slide-cross, slide-cross-slide and running Steps) were classified by front row position and type of set. The non-parametric chi-square analysis was performed to detect differences among genders, outside blocker positions and direction of movement. The results have shown significant differences (p<0.001). Moving laterally äs middle blockers, women use more Steps than men; female outside blockers frequently use the slide step while men use the cross step äs principal footwork technique. The reasons for these differences are discussed in the article. In male Volleyball, sets to outside hitters are faster: a smaller number of Steps can be made by blockers. Female Volleyball has the same trend: the use of cross techniques will increase in the future among women too. Some special exercises have been selected and suggested to better train players in blocking movements.